Novel membrane-based targets – Therapeutic potential in gynecological cancers. Issue 3 (March 2015) - Gizzi, M.; Pautier, P.; Lhomme, C.; Leary, A.
Abstract Recent advances have been made in the molecular profiling of gynecological tumors. These discoveries have led to the development of targeted therapies that have the potential to disrupt molecular pathways involved in the oncogenesis or tumor progression. In this review, we highlight areas of recent progress in the field of membrane receptor inhibitors in gynecological malignancies and describe the biological rationale underlying the inhibition of these receptors. We will introduce drug immuno-conjugates, and give an update on the biological rationale and the clinical studies involving agents directed against EGFR, HER3, IGFR, MET, FGFR, NOTCH, and TRAIL. We also discuss the challenge facing these new therapies.